Bentuk Penyajian Tari Gambyongan Srampat Tayub di Desa Jimbe Kecamatan Kademangan Kabupaten Blitar - Dwiwahyuni, Isti; Zandra, Rully Aprilia (Universitas Negeri Medan, 2026)
This study aims to describe in depth and comprehensively the three main components of the presentation form of the Gambyongan Srampat Tayub Dance in Jimbe Village, namely the theme, costume, and make-up, considering the decreasing number of artists who master the structure of the dance and the lack of regeneration. This study uses observation, interview, and documentation data collection techniques, using Jazuli's theory on the form of presentation. The results of the study indicate that the theme of the Gambyongan Srampat Tayub Dance is derived from four elements, namely comments on life (expressions of joy and harmony), folklore (legends of colonial history and the Jimbe locality), the history of a figure (Ibu Sukarmi), and literary works (traditional songs with moral meaning). The costume forms the curves of the body and has aesthetic meaning. Meanwhile, the make-up does not use character make-up but rather beautiful make-up. This study contributes to filling the gap in the study of the theme of the Gambyong Srampat Tayub dance and provides a comprehensive understanding that has urgency for efforts to preserve local culture among the younger generation.